2017
DOI: 10.13189/iid.2017.050202
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Investigation of Foot and Mouth Disease and Serotype Identification of the Viruses in Cattle of Bangladesh

Abstract: Foot and Mouth Disease (FMD) is a highly contagious viral disease of farm animals. This study was aimed to identify symptoms, characteristics pathology and viral serotypes involved in infected cattle of Bangladesh. Dominant signs observed were salivation, vesicular eruption, lameness and maggot infestations in 66%, 80%, 36% and 14% cattle respectively. Out of 202 infected cattle investigated, 35 were below six months of age. A total of 18 young calves and 8 adult cattle were died due to FMD. Seven young calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Histopathological findings in the lungs revealed pulmonary congestion and edema, similar to the findings of recent studies [ 34 ]. Neurogenic pulmonary edema has been explained by an increase in pulmonary vascular pressure due to sympathetic stimulation, with a subsequent increase in pulmonary endothelial permeability [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…Histopathological findings in the lungs revealed pulmonary congestion and edema, similar to the findings of recent studies [ 34 ]. Neurogenic pulmonary edema has been explained by an increase in pulmonary vascular pressure due to sympathetic stimulation, with a subsequent increase in pulmonary endothelial permeability [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…Salguero et al (2005) observed lesions on the lips of mice after 24 hours of infection and similar findings were observed in the present results. The erosive epithelium on the lips and vesicles on the footpads of mice were similar to those reported in large animals by Islam et al (2017) but after that, the mice showed a recovery stage as the death rate declined. In the first 48 hours, out of 45 experimental animals, seven died and after 72 hours, five mice died.…”
Section: Statistical Resultssupporting
confidence: 84%
“…This virus, together with the other viral factors' constant change in attributes, makes it challenging for specialists in this sector to battle the disease (Rahman et al, 2022). According to RT-PCR, FMDV serotypes O, A, and Asia-1 are actively prevalent in Bangladesh (Islam et al, 2017). Combined infection of Type A and Asia-1 FMDV was also discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Combined infection of Type A and Asia-1 FMDV was also discovered. From 1960 to 1990, a seroepidemiological examination of this virus in the cattle population discovered that four different varieties (A, O, C, and Asia-1) of FMDV were common in Bangladesh (Islam et al, 2017). FMDV serotypes A and O were prevalent in this country between 1996 and 2000 (Islam, 2001) .…”
Section: Introductionmentioning
confidence: 99%